In vitro and in vivo Antidiabetic Activity of Ag Nanoparticles Mediated from Gymnemic Acid I and II - Sivaramakumar, Navanita; Shanker, Kalakotla (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Gymnema sylvestre is traditionally used to treat diabetes in Asia. Materials and methods: GA-I and GA-II were docked to PTP 1B. Nanoparticles were produced using centrifugation green synthesis. Results: Blood glucose levels significantly decreased (p less than 0.001) at a dose of 200 mg/kg of GA-I mediated AgNPs. Conclusion: GA-I mediated AgNPs can be exploited as prospective nanomedicine for type-2 diabetes.
Keywords: Gymnemic Acid-I; Molecular docking; PTP 1B